Padel vs. tennis doubles: a comparison of performance demands and game attributes - Paulauskas, Rūtenis; Šakinis, Domantas; Figueira, Bruno (Frontiers in Sports and Active Living, 2025)
IntroductionThis study investigates differences in performance demands and match characteristics between padel and tennis doubles.MethodEight national-level male players (age of 27.0 ± 7.4 years, height of 186.3 ± 7.7 cm, body mass of 81.5 ± 10.7 kg, training frequency of tennis 4.8 ± 1.6 and padel 4.9 ± 1.4 h/week) participated in a total of 12 simulated matches, consisting of six tennis doubles and six padel sessions. The sessions were analyzed to assess various performance and physiological metrics. Match analysis focused on rally duration, strokes per rally, and movement characteristics, measured through standardized methods. Statistical comparisons were conducted using linear mixed models to identify significant differences between performance demands and match characteristics that define Padel and Tennis players.ResultsResults indicate that tennis involves greater movement distances, higher speeds, more sprints, and longer rest intervals between rallies. In contrast, padel matches featured a higher total number of rallies, more frequent volleys and ground strokes, and longer play durations. All variables compared between Tennis and Padel showed statistical differences (p < 0.05). Despite these disparities, average heart rate and lactic acid responses were comparable across both sports, indicating similar physiological demands.DiscussionThese findings highlight the importance of sport-specific training regimens tailored to the unique requirements of each sport. Practical applications include optimizing training to enhance endurance and tactical adaptability for Padel players, while emphasizing explosive power and recovery strategies for Tennis athletes.